Cenário de práticas empresariais em inteligência competitiva na indústria de telecomunicações - Zenaide, Vitor Rodrigues (2012)
This paper aims to apply the theoretical framework Wright-Pickton in Competitive Intelligence (CI) to the reality of this practice in Brazilian companies of the telecommunications industry, in order to create a diagnostic of the current situation of CI and improve the theoretical model, seeking to make it more accurate to evaluate CI processes in organizations. From this diagnosis, some recommendations for the CI function upgrading were made as a product of this dissertation, making it fundamental for the decision-making process. It was used the same methodology of an article published in 2009 that investigated the reality of CI activities on retail banks in United Kingdom from the same framework. In this study, the focus was the telecommunications industry, covering the entire value chain. The information collection was based on interviews with executives that lead departments or functions related to the Competitive Intelligence concept. As a final result, it was realized that the aspects of data collection and CI outputs use were the most distant from the ideal situation considered by the framework, attributes that can be improved to make a better connection of the practice with the company strategy.